2022
DOI: 10.1371/journal.pone.0274480
|View full text |Cite
|
Sign up to set email alerts
|

IDEST: International Database of Emotional Short Texts

Abstract: We introduce a database (IDEST) of 250 short stories rated for valence, arousal, and comprehensibility in two languages. The texts, with a narrative structure telling a story in the first person and controlled for length, were originally written in six different languages (Finnish, French, German, Portuguese, Spanish, and Turkish), and rated for arousal, valence, and comprehensibility in the original language. The stories were translated into English, and the same ratings for the English translations were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…Perceived aggression was an important variable in prediction of the victorious individual. In the research by Kaakinen et al (2022), it was found that based on the experienced arousal, the process of reading texts is impacted. The arousal makes it difficult to read texts and may emerge from the negative experience or aggressiveness of the text.…”
Section: Perceived Aggressiveness and Experienced Arousalmentioning
confidence: 99%
“…Perceived aggression was an important variable in prediction of the victorious individual. In the research by Kaakinen et al (2022), it was found that based on the experienced arousal, the process of reading texts is impacted. The arousal makes it difficult to read texts and may emerge from the negative experience or aggressiveness of the text.…”
Section: Perceived Aggressiveness and Experienced Arousalmentioning
confidence: 99%